Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Produk Hand and Body Lotion Vaseline Dengan Brand Image Sebagai Variabel Intervening (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Dharma Andalas) - Putri Dewita Sari; Yesi Elsandra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the effect of brand ambassadors on purchasing decisions for Vaseline hand and body lotion products with brand image as an intervening variable. This study uses a quantitative research method with a population of students from the Faculty of Economics and Business, Dharma Andalas University. The sample was determined by the non-probability sampling method using a purposive sampling technique with a sample size of 92 respondents. Data were analyzed using SmartPLS version 4 software with Structural Equation Model (SEM) modeling. The results showed that brand ambassadors had a positive and significant effect on brand image. In addition, brand ambassadors also had a positive and significant effect on purchasing decisions. Brand image itself has been shown to have a positive and significant effect on purchasing decisions, and brand ambassadors also influence purchasing decisions through brand image as an intervening variable. This shows that brand image has an important role in strengthening the relationship between brand ambassadors and purchasing decisions for Vaseline hand and body lotion products.